In silico study of Sambiloto (Andrographis paniculata) compounds from GC-MS and LC-MS/MS as alpha-glucosidase and DPP-4 enzyme inhibitor - Kusriani, Herni; Purwaniati, Purwaniati; Bintang, Muhamad Ilham (Universitas Ahmad Dahlan, 2024)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia, impaired insulin secretion, and insulin action. To overcome this disease, some people treat it with natural ingredients. Sambiloto (Andrographis paniculata) is reported to have a wide range of pharmacological activities, one of which is anti-diabetic. Sambiloto showed activity in lowering blood glucose which has the potential as an antidiabetic. Computational methods, such as molecular docking, can increase the effectiveness and reduce the cost of searching for new active compounds. The purpose of this study was to determine the component compounds contained in the ethanol extract of Sambiloto and obtain the potential compounds to inhibit the alpha-glucosidase and DPP-4 enzymes as anti-diabetics with molecular docking method. Sambiloto leaves were macerated for 3 x 24 hours using ethanol 96% as a solvent and concentrated with an evaporator. Sambiloto extract was analyzed using LC-MS, and GC-MS. In-silico analysis includes geometry optimization and molecular docking methods. Preparation of the test ligands was carried out by the ChemBioDraw Ultra and ChemBio3D applications, then optimization by Gaussian 09 application. The crystal structures of the target proteins used were those with PDB ID 5NN8 for alpha-glucosidase and 2QOE for DPP-4. Molecular docking was performed using Autodock 4.2.3 application. From analysis with LC- MS/MS and GC-MS methods, 18 compounds were identified. Molecular docking was performed on the identified compounds. The results of molecular docking showed that the compound S17 (11-(P- Bromoanilino)-5H-Dibenzo [B,E] [1,4] Diazepine), S1 (andrographolide) and S2 (andrographanin) have the potential to inhibit the activity of alpha-glucosidase enzyme; on the other hand S17 (11-(P-Bromoanilino)-5H-Dibenzo [B,E][1,4]Diazepine) and S5 (andrographolactone) have the potential to inhibit the activity of DPP-4 enzyme. These compounds have the potential to inhibit alpha- glucosidase and DPP-4 enzymes which act as antidiabetics.